1991
DOI: 10.1155/tsm.14-18.915
|View full text |Cite
|
Sign up to set email alerts
|

Rolled textures and Magnetic Properties of Regular Grain Oriented 3% Silicon Steel With Very Low Thickness

Abstract: Regular grain oriented 3 wt.% silicon steel of 0.30ram thick, having orientations rear (110)[001], were eold roiled to 0.050ram thick and their 0.100 and 0.050ram thick foils were annexed in order to study changes in rolled textures, recrystalliz textures and magnetic properties with decreasing tl sheet thickness. The results are summ as follows: (110)[001] grains of reerystalliz sheets are changed to (111)[112] with cold rolling and (111)[112] grains of eold rolled sheets are red to(ll0)[001] with annealing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The origin of the Goss texture obtained after recrystallization during the Goss industrial processing [3] of the grain oriented Fe-3%Si alloy was widely investigated [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. On one hand, many investigations on single or poly crystal of Fe-Si alloy showed that the Goss texture of the primary recrystallization develops by the inheritance of this texture from hot rolling [4,11].…”
Section: Introductionmentioning
confidence: 99%
“…The origin of the Goss texture obtained after recrystallization during the Goss industrial processing [3] of the grain oriented Fe-3%Si alloy was widely investigated [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. On one hand, many investigations on single or poly crystal of Fe-Si alloy showed that the Goss texture of the primary recrystallization develops by the inheritance of this texture from hot rolling [4,11].…”
Section: Introductionmentioning
confidence: 99%